An Active Teaching Approach for Fetal and Maternal Assessment in Delivery Room: A Randomized Clinical Trial - Shahla Mohamadirizi; Parvin Bahadoran; Soheila Mohamadirizi (Mashhad University of Medical Sciences, 2017)
ABSTRACTBackground: A modern teaching method has been used for educating the midwifery students. Regarding the importance of accuracy and speed among the midwifery students, especially in the stressful condition of childbirth, this study aimed to investigate the effect of time management and precaution techniques on the midwifery student's clinical performance in the labour ward.Methods: This study was conducted on 40 midwifery students during November 2015-March 2016. The participants were randomly assigned into the control and experimental groups that were trained using the traditional method and time management techniques, respectively. The subjects' clinical performance regarding the fetal heart rate monitoring, contraction check, and physical examination was assessed using a checklist during the intervention and four months after the intervention. The data analysis was performed using the independent and paired t-tests through the SPSS version 14. P-value less than 0.05 was considered statistically significant.Results: According to the results of the present study, there was no significant difference between the two groups regarding the speed of performing the examined clinical care before the intervention. However, following the intervention, there was a significant difference between the two groups in this regard (P=0.010). Additionally, the paired t-test revealed a statistically significant difference in the speed of performing the clinical care between the two groups after the intervention (P=0.018).Conclusion: As the findings of the present study indicated, the time management technique could improve the speed in the midwifery students. Therefore, this technique as a modern method is recommended to be employed in the emergency wards such as the labour and delivery wards.